THE ROLE OF IN-HOUSE TRAINING ACTIVITIES IN IMPROVING TEACHER PEDAGOGIC COMPETENCE - Dini Anggraeni; Ari Riswanto (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
Pedagogic competence is one of the main competencies that must be possessed by a teacher. Having pedagogical abilities will help the professionalism of teachers, so that they become different from other professions. However, it is still a problem when teachers have not mastered these competencies, it can be seen from the number of teachers who have difficulty understanding the characteristics of students or teachers have not been able to arrange meaningful learning activities. So that teaching and learning activities are only limited to presenting learning material. From some of these problems, researchers conducted research on one of the activities aimed at improving the pedagogic competence of teachers. This activity is often called In House Training. The purpose of this study was to determine the increase in teacher pedagogic competence through In House Training activities at the Integrated Islamic Elementary School in Sukabumi City. The research method uses descriptive qualitative. The data collection techniques used were observation, interviews and field notes presented through discussion descriptions. The results of the study indicate that the existence of In-House Training activities can improve the pedagogic competence of teachers.